Offsetting and the Consumption of Social Responsibility - Ezra Rosser (Washington University Law Review, 2011)
This Article examines the relationship between individual consumption and consumption-based harms by focusing on the rise in consumption offsetting. Carbon offsets are but the leading edge of a rise in consumer options for offsetting externalities associated with consumption. Moving from examples of quasi offsetting to environmental offsetting and the possibility of poverty offset institutions, I argue that offsetting provides a valuable mechanism for individuals to correct for the harms associated with consumption. This Article makes two major contributions to how we understand the relationship between consumption and social responsibility. First, it identifies an emerging offsetting phenomenon in seemingly discrete market practices and gives suggestions for improving upon them. Second, it suggests that by taking seriously both consumption and externalities, progress can be made on everything from the environment to global poverty. Offsetting, while not getting at all moral or societal obligations, does root such obligations in the shared activity, and perhaps belief, of Americans: consumption.
Keywords: Carbon offsets; Consumption (Economics); Corporate social responsibility; United States